PERAN KELOMPOK KEAGAMAAN DALAM PEMELIHARAAN KERUKUNAN UMAT BERAGAMA (Studi Kasus Desa Adat Angantiga, Petang, Badung, Bali) - Ibnu Hasan Muchtar (Harmoni, 2013)
In the last two years, emerging the controversy on the existence of mass organization / groups that are considered as the troubling group because it`s often considered doing anarchic acts. This group is very small compared with the group /mass organization which is very tolerant, open and supporting the religious harmony but mostly unexposed. This research wants to showing them which is large in number, one of them in the Angantiga Village.